2016
DOI: 10.5851/kosfa.2016.36.5.635
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cronobacter sakazakii by Lactobacillus acidophilus n.v. Er2 317/402

Abstract: Lactobacillus acidophilus n.v. Er2 317/402 strain Narine is known as a health beneficial functional probiotic culture and supplementary source of nutrition for newborns. In this study, in vitro antimicrobial activities of Narine-lyophilized (Narine-L), Narine-heat treated (Narine-HT), and Narine crude cell-free extract (Narine-CCFE) were evaluated against pathogen Cronobacter sakazakii (C. sakazakii) in agar as well as in a reconstituted powdered infant formula (RPIF) model. Inhibition zones of 30 mg Narine-L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…C.sakazakii it is an opportunistic human and food-borne pathogen. The organism can be found in broad range of food including powdered infant formula (PIF) , cheese, meat, vegetables, grain, herbs , spices , tomato , water and households [23,24] These results coincides with pervious study which shown that Lactobacillus acidophilus has ability to inhibit and safe bio-preservative protect infants from C.sakazakii [25,26].…”
Section: Antimicrobial Effect Of Lacidophilus Against Three Isolatedsupporting
confidence: 75%
“…C.sakazakii it is an opportunistic human and food-borne pathogen. The organism can be found in broad range of food including powdered infant formula (PIF) , cheese, meat, vegetables, grain, herbs , spices , tomato , water and households [23,24] These results coincides with pervious study which shown that Lactobacillus acidophilus has ability to inhibit and safe bio-preservative protect infants from C.sakazakii [25,26].…”
Section: Antimicrobial Effect Of Lacidophilus Against Three Isolatedsupporting
confidence: 75%
“…Growing concerns over emerging antibiotic resistance coupled with the high risk of Cronobacter sakazakii infections in formula-fed infants have led to new studies investigating the efficacy of postbiotics produced by different probiotic strains against C. sakazakii [ 90 ]. For instance, lyophilized and heat-treated probiotic Lactobacillus acidophilus INMIA 9602 Er 317/402 (strain Narine) proved to inhibit the growth of C. sakazakii in contaminated reconstructed powdered infant formula after coculture for 6 h at 37 °C [ 65 ]. However, when employing the agar well diffusion method, CFS Narine was the most effective in inhibiting C. sakazakii growth compared to lyophilized and heat-treated Narine.…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
“…Antimicrobial effects were attributed to antimicrobial peptides (caseicin A & B) derived from the degradation of bovine casein by microbial enzymes. Charchoghlyan et al (89) found that a purified heat inactivated aqueous extract of skim milk fermented with a commercial probiotic strain of Lactobacillus acidophilus used to supplement PIF also inactivated C. sakazakii in the reconstituted product stored at 37 • C. The composition of the extract was not provided by the authors of the study, who offered that acids released during fermentation were likely responsible for antibacterial effects. A similar conclusion was reached by Kim et al (90) derived from any microbial species is a barrier to broader food applications.…”
Section: Introductionmentioning
confidence: 99%